2017
DOI: 10.1002/gps.4682
|View full text |Cite
|
Sign up to set email alerts
|

Housing First for older homeless adults with mental illness: a subgroup analysis of the At Home/Chez Soi randomized controlled trial

Abstract: Housing First significantly improved housing stability among older and younger homeless adults with mental illness, resulting in superior mental health and quality of life outcomes in older homeless adults compared with younger homeless adults at 24 months. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…Given that 95% of the sample was stably housed at the 12‐month follow‐up, this may suggest that housing itself is a facilitator of positive changes in mental health symptomatology for formerly homeless adults. These findings are consistent with a recent PSH evaluation study of Los Angeles‐based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, ) and two studies of Canadian‐based PSH residents that found mental health improved in housing (Chung et al, ; Gadermann et al, ). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Given that 95% of the sample was stably housed at the 12‐month follow‐up, this may suggest that housing itself is a facilitator of positive changes in mental health symptomatology for formerly homeless adults. These findings are consistent with a recent PSH evaluation study of Los Angeles‐based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, ) and two studies of Canadian‐based PSH residents that found mental health improved in housing (Chung et al, ; Gadermann et al, ). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionsupporting
confidence: 88%
“…Angeles-based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, 2017) and two studies of Canadian-based PSH residents that found mental health improved in housing (Chung et al, 2018;Gadermann et al, 2015). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four studies reported mental health outcomes; these were categorised as ‘self-rated mental health’ (n=3: At Home, Chicago Housing for Health Partnership (CHHP) and Housing Opportunities for Persons with AIDS (HOPWA)) and ‘severity of mental health symptoms’ (n=3: At Home, Pathways Housing First (PHF) and HOPWA). Two studies provided data eligible for meta-analysis of self-rated mental health (At Home and CHHP)43 44; a very small improvement was seen in intervention groups compared with treatment as usual (SMD=0.07; 95% CI −0.19 to 0.33; p=0.60, I 2 =82%; figure 3A). Additionally, HOPWA reported no statistically significant difference between groups 45.…”
Section: Resultsmentioning
confidence: 99%
“…Regarded by Canadian and U.S. federal governments as an evidence-based strategy to ending homelessness (Government of Canada, 2014; U.S. Interagency Council on Homelessness, 2015), Housing First has been found to increase housing stability and improve quality of life for program participants (Chung et al, 2018;Patterson et al, 2013). As a result, Housing First has become a primary initiative in Canada and the U.S. in the provision of permanent independent housing to individuals who are experiencing homelessness who have multiple barriers to housing, such as mental health problems and substance use disorders (Tsemberis & Eisenberg, 2000).…”
Section: Research Contextmentioning
confidence: 99%